Statement by H. E. Dilma rousseff, President of the Federative Republic of Brazil, at the opening of the general debate : Of the 67th session of the United Nations General Assembly. New York, 25 September 2012 - Centro de Estudios Sudamericanos (2012)
Once again, a woman's voice is opening the debate of the United Nations General Assembly. For many, we women are "half the sky". But we want to be half of the Earth as well. With equal rights and opportunities. Free from all forms of discrimination and violence. Capable of building our own emancipation and, with it, of contributing to the emancipation of all. (Párrafo extraído del texto a modo de resumen)